2012
DOI: 10.1016/j.brs.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain blood-flow change with acute vagus nerve stimulation in treatment-refractory major depressive disorder

Abstract: Background Existing neuroimaging studies of vagus nerve stimulation (VNS) in treatment resistant major depression (TRMD) suggest that many brain regions (e.g., prefrontal cortex, thalamus, cingulate cortex, insular cortex) associated with mood disorders undergo alterations in blood flow/metabolism. Objective/Hypothesis Positron emission tomography (PET oxygen-15 labeled water or PET [15O] H2O) was used to identify changes in regional cerebral blood flow (rCBF) in response to immediate VNS in 13 subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…The lateral OFC receives afferent projections from the nucleus tractus solitarius, the principal terminus of interoceptive inputs from the vagus nerve, and potentially acts through the perigenual ACC to regulate visceromotor activity (Conway et al, 2012;Thayer et al, 2012). The reciprocal relationship between the vagus nerve and the mPFC may have implications for the regulation of the immune system, which is putatively disturbed in mood disorders (Dantzer et al, 2008;Irwin and Cole, 2011;Miller et al, 2009;Padmos et al, 2008;Savitz et al, 2013a).…”
Section: Discussionmentioning
confidence: 98%
“…The lateral OFC receives afferent projections from the nucleus tractus solitarius, the principal terminus of interoceptive inputs from the vagus nerve, and potentially acts through the perigenual ACC to regulate visceromotor activity (Conway et al, 2012;Thayer et al, 2012). The reciprocal relationship between the vagus nerve and the mPFC may have implications for the regulation of the immune system, which is putatively disturbed in mood disorders (Dantzer et al, 2008;Irwin and Cole, 2011;Miller et al, 2009;Padmos et al, 2008;Savitz et al, 2013a).…”
Section: Discussionmentioning
confidence: 98%
“…The vagus nerve is a mixed nerve composed of approximately 80% afferent fibers. It is speculated that the antidepressant effects of VNS are attributed partially to the projection of afferent fibers to the nucleus tractus solitaries (NTS), which is further connected both directly and indirectly with brain structures such as amygdala, hypothalamus, insula, thalamus, orbitofrontal cortex, and other limbic regions responsible for mood and anxiety regulation (Conway et al, 2012; Conway et al, 2006; Lomarev et al, 2002; Mu et al, 2004). An animal study (He et al, 2013) has shown that stimulating the auricular branches of the vagus nerve can significantly suppress epileptiform activity via the NTS in rats, which further endorses the effect of taVNS.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, brain-imaging tools have been applied to investigate the fMRI signal change evoked by VNS (Conway et al, 2013; Conway et al, 2012; Conway et al, 2006; Landau et al, 2015) and taVNS (Dietrich et al, 2008; Kraus et al, 2007; Kraus et al, 2013). In a previous study (Kraus et al, 2013), Kraus and colleagues investigated the anterior and posterior wall of the auditory canal separately.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with treatment-refractory major depressive disorder, CBF decreases (left and right lateral orbitofrontal cortex, left inferior temporal lobe) and increases (right dorsal anterior cingulated, left posterior limb of internal capsule/medial putamen, right superior temporal gyrus, left cerebellar body) were seen in different anatomical regions after VNS (32). …”
Section: Discussionmentioning
confidence: 99%